Determinants of Teachers’ Job Satisfaction: School Culture Perspective - Bahir Adem Abdulahi (Humaniora, 2020)
The main purpose of this paper was to describe the effect of school culture factors on teachers’ job satisfaction. Descriptive correlation design with mixed data approach was employed in four public secondary schools of Harari regional state, Ethiopia. The specific objectives were to describe the status of school culture and teachers job satisfaction, to identify the relationship between teachers’ job satisfaction and school culture, to investigate the effect of school culture on teachers’ job satisfaction and to sort out the determinants. The data information was gathered from teachers and educational leaders using questionnaire and interview guides respectively. Teachers’ level of job satisfaction was low. There was no relationship between teachers’ educational qualifications and their levels of job satisfaction. The relationship of teachers’ job satisfaction in terms age, sex, salary, working experience, and marital status was not significant. There was association between teachers’ job satisfaction and school culture, specifically with teachers’ professional development and collaborative leadership practices. School culture and teachers’ levels of qualification were predictors of job satisfaction in the schools. In order to enhance job satisfaction of teachers, the school leaders should strengthen and improve the existing continuous professional development program and collaborative leadership practices in the schools. Supervisors should support and facilitate professional development opportunities for teachers. Moreover, they should promote collaborative leadership practices in the schools. Future studies need to be considered in order to generalize the findings in different settings. Also undertake studies on the effect of job satisfaction and school culture on the quality of teaching-learning.